The Role of TikTok Content Personalization on Wardah Beauty Official Product Purchase Decisions - Bayu Hari Prasojo; Dwi Cahya Yuniar (International Journal on Orange Technologies, 2026)
This study aims to analyze the influence of TikTok content personalization on the purchase decision of Wardah Beauty Official products. The three main indicators of personalization analyzed include content relevance, content suitability and satisfaction with user preferences, and the frequency of content appearing on For You Page (FYP) pages. The method used was quantitative explanatory, with data collection techniques through an online questionnaire to 88 respondents who had been exposed to Wardah content on TikTok Shop. The analysis was carried out using a multiple linear regression model assisted by SmartPLS. The results showed that the three variables of content personalization did not have a significant effect on purchasing decisions. This shows that even though content has been personalized, it is not necessarily able to encourage consumers to make a purchase. These findings imply the need for a more comprehensive marketing approach to create purchase conversions on social media platforms like TikTok.